Cgnz1 allele confers kidney resistance to damage preventing progression of immune complex–mediated acute lupus glomerulonephritis - Ge, Yan; Jiang, Chao; Sung, Sun-Sang J.; Bagavant, Harini; Dai, Chao; Wang, Hongyang; Kannapell, Carol C.; Cathro, Helen P.; Gaskin, Felicia; Man Fu, Shu (The Journal of experimental medicine, 2013)
Cgnz1 and Agnz1 on the distal region of mouse chromosome 1 are associated with chronic glomerulonephritis (cGN) and acute GN (aGN). NZM2328.Lc1R27 (R27) was generated by introgressing a C57L/J region where Cgnz1 is located to NZM2328. R27 female mice developed aGN mediated by immune complex (IC) deposition and complement activation without progression to cGN with severe proteinuria. End stage renal disease (ESRD) was not seen in R27 mice as old as 15 mo. Thus, aGN and cGN are under separate genetic control, and IC-mediated proliferative GN need not progress to cGN and ESRD. NZM2328 and R27 female mice have comparable immune and inflammatory parameters. In contrast to NZM2328, R27 mice were resistant to sheep anti–mouse GBM serum-induced nephritis, supporting the hypothesis that aGN is mediated by autoimmunity and resistance to the development of cGN is mediated by end organ resistance to damage. Thus, autoimmunity should be considered distinct from end organ damage. The Cgnz1 region has been mapped to a 1.34 MB region with 45 genes. Nine candidate genes were identified. Clinical relevance of these observations is supported by case studies. Clinical implications and the significance to human lupus and other diseases are presented.